Transformational Leadership of the Principal on Teacher Performance and School Quality - Moh. Ali (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the principal's leadership on teachers’ performance and school quality. This study used a qualitative approach with the type of research literature study. In the literature study in this study there are several stages that need to be done, namely cutting the source of literartures on the same topic, then sorting the literature with a certain grace period, then choosing search results that match the theme and title to be researched for reference. Data is obtained through literature, notebooks, magazines, and other references as well as relevant research. Data analysis can be adjusted to the research objectives, and the stages are deductive, inductive, interpretive, comparative, historical. From the results of the study, it is clear that the transformational leadership of the principal is very influential on improving teacher performance and school quality.